Islam : Faith, Culture, History - Lunde, Paul (London Dorling Kindersley, 2002)
Includes a section of profiles of the "leading Muslim countries of the world today."
Include Color Illustrations, Color Maps and Index
Keywords: Islam -- Islamic civilization -- Islamic countries